THE PSYCHOLOGICAL FACTORS AFFECTS ONLINE BUYING BEHAVIOUR - Nuradina, Kartika (Universitas Indonesia Membangun (Inaba), 2022)
In the last five years, consumer behaviour has transformed from offline buying to online buying. There are various factors which affect why such a phenomenon happened. For example, there is the influence of external factors such as technological development, social change, pandemic situation, and modern lifestyle. On the other hand, internal factors such psychological aspects can also affect the change in the shift towards online buying style. This study provides a systematic review of consumer behaviour in online retailing, based on literature review of online consumer behaviour in the field of marketing and business, published in international peer-reviewed journals between periods of 2015 to 2020. This study highlighted the importance of psychological factors such as perception and attitude, motivation, emotion, trust as the factors which influence the transformation towards online buying. Further discussion was also done in regards to the psychological factors based on the psychological and consumer behaviour theoretical framework. The purpose of this article is to gain a comprehensive understanding of the psychological factors that can influence consumers in making online purchases of goods. Based on the findings from this study, insights for future research is presented for academics, as well as important points for practitioners and professionals in terms of understanding psychological factors that can influence the purchase decisions made by consumers.